Strategic human resource leader : how to prepare your organization for the six key trends shaping the future - Rothwell, William J., 1951-; Prescott, Robert K.; Taylor, Maria W. (Palo Alto, Calif. : Davies-Black, 1998)
The need to seize the future. Examining the trends. Taking action...
Keywords: Personnel management; Personnel management